Strategi Koperasi Karya Mandiri Dalam Memperkenalkan Product Knowledge Melalui Event Gowes Pesona Nusantara - Erik Maudi; Susilowati Susilowati (Jurnal Komunikasi, 2018)
Cooperative function amid the current society it is necessary as a support to the economy of certain community groups in order to build and develop the economic potential of the community. Koperasi Karya Mandiri following the participation of the event "Cycling the Charm of Archipelago" organized by the Government of the city of South Tangerang and the Ministry of Youth and Sports in order to introduce the products to their advantage. The author uses descriptive-qualitative research methods, conducted by means of observation and in-depth interviews in person, as well as the data collected are then analyzed in the report form through the descriptive research. The conclusions of the research implemented by the author show that the Koperasi Karya Mandiri through participation at Cycling the Charm of Archipelago event, Cooperatives in Indonesia now can not be considered one eye because it was now more developing services and products that are already adapting with the times now namely convenience, Koperasi Karya Mandiri implements the event participation program in order to expand its wings and inspire the general public, especially the people of Tangerang Selatan and people with disabilities through Knowledge Koperasi Karya  Mandiri products that fill the exhibition of SME (Small and Medium Enterprises) at the event.Keywords: Strategy, Product Knowledge, Participation